Driving forces behind changes in the aggregate labour force participation in Hungary - Gábor Kátay; Benedek Nobilis (Magyar Nemzeti Bank, 2009)
This paper proposes a simple and transparent methodology for decomposing changes in the aggregate labour force participation rate over time into changes in the labour force participation behaviour of different population groups and changes in each group's population share. Unlike traditional decomposition methods based only on demographic factors, our approach also identifies the contribution of all major factors that can account for the developments in the labour force participation such as change in the general educational level or the most important social welfare programs. An application on Hungarian labour force data shows that the selected variables explain the evolution of the participation rate quite well - especially on the long term. More specifically, our results indicate that the rising labour supply since '97 in Hungary was principally driven by the increasing average level of education and, most importantly, the gradual tightening of the conditions of old-age retirement. The other estimated effects are also in line with our expectations. Given that the residual term not captured by the model has no visible trend but fluctuates with economic cycles, the explained part can also be interpreted as an indicator of the underlying labour supply.
Keywords: J11; J21; J22; J26; 330; labour force participation; decomposition; demographic change; schooling; social transfers; Erwerbstätigkeit; Arbeitsangebot; Ungarn